FAKTOR PENDORONG DAN PENARIK MIGRASI SUKU KOMERING - Dera Elfranita; Buchori Asyik; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this study examines the push and pull factors of migration ratesHistories and Korto Betung Village to East Village Gumawang Oku district. Studieson the pressure point of dissatisfaction in the area of origin, limited employmentopportunities, expectations of better economic life, and the business opportunities inthe goal area.This study uses descriptive exploratory. Population of this study is as much as 45migrant families, all as respondents in the study (total population). Data was collectedthrough observation and interview techniques, questionnaires and documentation.Data analysis was performed with a table and as a percentage of the basicinterpretation and description in a research report.The results showed: (1) A total of 60.00% of respondents stated migrate due todissatisfaction in the area of origin. (2) A total of 82.22% of the respondents migratedbecause of limited job opportunities in the area of origin. (3) as much as 86.67% ofrespondents expressed migrate because of the expectations of a better economic lifeat the destination. (4) as much as 82.22% of respondents migrated due to new andbetter earnings at the destination.Keyword : Migration, push and pull factor